2016
DOI: 10.1038/srep19032
|View full text |Cite
|
Sign up to set email alerts
|

Western diet induces a shift in microbiota composition enhancing susceptibility to Adherent-Invasive E. coli infection and intestinal inflammation.

Abstract: Recent advances have shown that the abnormal inflammatory response observed in CD involves an interplay among intestinal microbiota, host genetics and environmental factors. The escalating consumption of fat and sugar in Western countries parallels an increased incidence of CD during the latter 20th century. The impact of a HF/HS diet in mice was evaluated for the gut micro-inflammation, intestinal microbiota composition, function and selection of an E. coli population. The HF/HS diet created a specific inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
304
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 386 publications
(322 citation statements)
references
References 42 publications
12
304
1
5
Order By: Relevance
“…Similarly, according to Agus et al 22 , excessive consumption of animal protein is associated with an increased risk of developing CD; while the consumption of fruit and vegetables was inversely related 15 . Patients with CD also showed a shift in the microbiota, with an increased Proteobacteria and Bifidobacteria groups, and a decreased Firmicutes 22 . For UC, in addition to the large consumption of refined carbohydrates and simple sugars, the consumption of large amounts of fatty acids is also associated with an increased risk 17 .…”
Section: How Nutrition and Diet Can Influence Microbiota And Correct mentioning
confidence: 89%
See 3 more Smart Citations
“…Similarly, according to Agus et al 22 , excessive consumption of animal protein is associated with an increased risk of developing CD; while the consumption of fruit and vegetables was inversely related 15 . Patients with CD also showed a shift in the microbiota, with an increased Proteobacteria and Bifidobacteria groups, and a decreased Firmicutes 22 . For UC, in addition to the large consumption of refined carbohydrates and simple sugars, the consumption of large amounts of fatty acids is also associated with an increased risk 17 .…”
Section: How Nutrition and Diet Can Influence Microbiota And Correct mentioning
confidence: 89%
“…Several studies have shown a correlation between increased oxidative stress and a Western-style diet rich in fats and refined sugars. These products in fact, if taken frequently and in large quantities, cause an increase of the inflammatory state with ROS production and subsequent amplification of the inflammatory cascade [21][22][23] . Currently, there are also discussions about the potential role of heat shock proteins (HSPs) in the pathogenesis of IBD.…”
Section: Dysbiosis and Related Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nas últimas décadas, o padrão alimentar sofreu grandes mudanças de composição, houve um aumento no consumo de produtos industrializados ricos em gordura e açúcares refinados (AGUS et al,2016).…”
Section: Introductionunclassified